The inverse-trans-influence in tetravalent lanthanide and actinide bis(carbene) complexes - Gregson, Matthew; Lu, Erli; Mills, David P.; Tuna, Floriana; McInnes, Eric J.L.; Hennig, Christoph; Scheinost, Andreas C.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Kerridge, Andrew; Liddle, Stephen T. (Nature Publishing Group, 2017)
Across the periodic table the trans-influence operates, whereby tightly bonded ligands selectively lengthen mutually trans metal–ligand bonds. Conversely, in high oxidation state actinide complexes the inverse-trans-influence operates, where normally cis strongly donating ligands instead reside trans and actually reinforce each other. However, because the inversetrans-influence is restricted to high-valent actinyls and a few uranium(V/VI) complexes, it has had limited scope in an area with few unifying rules. Here we report tetravalent cerium, uranium and thorium bis(carbene) complexes with trans C¼M¼C cores where experimental and theoretical data suggest the presence of an inverse-trans-influence. Studies of hypothetical praseodymium(IV) and terbium(IV) analogues suggest the inverse-trans-influence may extend to these ions but it also diminishes significantly as the 4f orbitals are populated. This work suggests that the inverse-trans-influence may occur beyond high oxidation state 5f metals and hence could encompass mid-range oxidation state actinides and lanthanides. Thus, the inverse-trans-influence might be a more general f-block principle.